Pengaruh Perawatan Metode Kangguru terhadap Kenaikan Berat Badan pada Bayi Berat Lahir Rendah RS. Assyifa Kota Sukabumi - Muhammad Ivan Muttaqin (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Low birth weight (LBW) infants are defined as newborns weighing less than 2500 grams, a condition that poses a high risk of various health complications. This study employed a quantitative approach with a pre-experimental design to examine the effect of Kangaroo Mother Care (KMC) on weight gain among LBW infants at Assyifa Hospital, Sukabumi City. The findings revealed that before receiving KMC, the majority of infants were categorized as LBW (10 respondents; 62.5%), while the remaining were very low birth weight (VLBW) (6 respondents; 37.5%). After the intervention, most infants remained in the LBW category (15 respondents; 93.8%), while one infant (6.3%) achieved a normal birth weight. Statistical analysis showed that the pre-intervention mean weight was 1658.50 grams with a standard deviation of 394.893. Following KMC, the mean weight increased to 2177.38 grams with a standard deviation of 239.806. Correlation testing indicated an r-value of 0.442 with a significance level of 0.087, while the paired sample test yielded a significance value of 0.000 (p < 0.05). These results indicate a significant improvement in infant weight after the implementation of KMC.Based on hypothesis testing, the null hypothesis (Ho) was rejected, confirming that Kangaroo Mother Care has a significant effect on the weight gain of LBW infants. This finding highlights KMC as a simple yet effective intervention to support the growth and health of LBW infants.